Designing living matter. Can we do better than evolution?. Issue 6 (30th July 2013) - Schuster, Peter
<x xml:space="preserve">Abstract</x> Thanks to substantial improvements in the theory of metabolic fluxes and the application of 13C isotope markers in experimental flux studies, Pareto efficiency of bacterial metabolism can now be determined and direct answers to the long standing questions of optimization according to multiple criteria in nature can be given. Cells or organisms operate close to Pareto optima but the performance with respect to every single criterion is almost always improvable. Rational design and evolutionary methods are routinely used for the production of biomolecules with optimized properties. Examples are proteins for technical applications, for example in detergents, and optimally binding nucleic acid molecules called aptamers. Among the various perspectives of synthetic biology, the usage of DNA for information storage is particularly promising: In a pilot experiment, an entire book including figures and a Java script, in total more than 5 megabit, were stored on a single DNA molecule. © 2013 Wiley Periodicals, Inc. Complexity 18: 21–31, 2013